2017
DOI: 10.1016/j.cub.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Facilitates Associative Learning and Alters Functional Connectivity in the Primate Brain

Abstract: There has been growing interest in transcranial direct current stimulation (tDCS), a non-invasive technique purported to modulate neural activity via weak, externally applied electric fields. Although some promising preliminary data have been reported for applications ranging from stroke rehabilitation to cognitive enhancement, little is known about how tDCS affects the human brain, and some studies have concluded that it may have no effect at all. Here, we describe a macaque model of tDCS that allows us to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 61 publications
7
117
1
Order By: Relevance
“…Furthermore, we know that tDCS modulates long-distance connectivity to subcortical structures (11). Hence, previous fMRI studies show that the DLPFC downregulates fear responses through projections to the vmPFC that in turn inhibit the amygdala during extinction learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we know that tDCS modulates long-distance connectivity to subcortical structures (11). Hence, previous fMRI studies show that the DLPFC downregulates fear responses through projections to the vmPFC that in turn inhibit the amygdala during extinction learning.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that fear experiences can be modulated by tDCS (4,5). The modulatory assumptions are that tDCS 1) induces cortical excitability and neuroplasticity, modulating long-term potentiation (LTP) and long-term depression (LTD) mechanisms (6,7); 2) its effects are polarity specific (8,9) in that anodal stimulation is excitatory, whereas cathodal stimulation is inhibitory when stimulating motor or parietal regions but inconsistent in other brain regions (10); 3) it interferes with the cortical and subcortical regions involved in fear learning networks and their connectivity patterns (11,12); and 4) its effects may persist over time (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…To date, TES research in small rodents predominantly utilizes currents at 100 to 200 µA peak-to-baseline (Grossman et al, 2017;Liebetanz et al, 2006;Monai et al, 2016;Pedron et al, 2014), while some work uses weaker inputs of 20-100 µA (Faraji et al, 2013;Wachter et al, 2011) or higher than 200 µA (Cambiaghi et al, 2011;Takano et al, 2011). TES in non-human primates typically operates at the intensity of 1-2 mA (Kar et al, 2017;Krause et al, 2017). The same intensity is most common in human studies and clinical applications (Antal et al, 2017;Paulus et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While some network models have predicted that such changes could produce changes in spike timing 33,45 , it was not clear whether tDCS would produce changes in firing rates. In fact, an earlier study did not detect firing rate changes 60 , perhaps due to the smaller sampling of neurons, or because only one lower intensity current was applied for shorter time intervals. We also found that firing rate responses were greater during the resting state as compared with the contracting phase of the task.…”
Section: Discussionmentioning
confidence: 84%